Forecasting Distributions of Variables with Seasonal Fluctuations - Zawadzki, Jan; Goc, Mateusz (O prognozowaniu rozkładów zmiennych wykazujących wahania sezonowe, 2010)
The following study presents the example of modelling and forecasting homogeneous distributions of the variable exhibiting seasonal fluctuations on the example of empirical distributions of the monthly unemployment rates by districts and cities with district rights in Poland. The study indicates that the process of creating the ex ante forecasts of distributions should be preceded by the ex post analysis of the accuracy of the forecasts of parameters and compliance of distributions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 195-207
Keywords: homogeneous distributions; forecasting; seasonal data